(untitled) (Journal of Health, Technology and Science (JHTS), 2023)
This study aims to find out the patient’s compliance level, the characteristics of pulmonary TB patients, and to find out the factors that affect compliance in outpatients at Kabila Health Center. The study was conducted using a quantitative approach, the population in this study is all outpatient tuberculosis patients at Kabila Health Center involving 28 sampling techniques used in this study are total sampling. This study is a descriptive study conducted observationally using research instruments, namely, The Informed Consent Form and the MMAS-8 Questionnaire. Data analysis is done using descriptive data analysis. From the results of the search of patient characteristics consisting of gender, age, education, and work, patients in Kabila health centers have a high level of adherence in the use of drugs for the healing process of TB disease. It can be seen in the results of the above study where the patient’s compliance rate obtained a high category of 23 people or 82.14% low 5 or 17.85%. Keywords: Compliance, Tuberculosis, Consuming OATS.